Dual Stimuli‐Responsive Nanoparticles for Controlled Release of Anticancer and Anti‐inflammatory Drugs Combination. Issue 39 (19th June 2017) - Feng, Liandong; Wang, Yuqi; Luo, Zhiliang; Huang, Zheng; Zhang, Yan; Guo, Kai; Ye, Deju
Abstract: Dual stimuli‐responsive nanoparticles capable of fine‐tuning drug release to augment therapeutic efficacy have become a promising tool for anticancer drug delivery. However, the rational design of these "smart" nanoparticles for a selective delivery and controlled release of multidrug combinations in cancer cells to achieve synergistic effects remain challenging. Here we report the pH/redox dual responsive nanoparticle FA‐DOX‐Ind‐NP (FA=folic acid, DOX=doxorubicin, Ind=indomethacin, NP=nanoparticle) based on the novel tumor targeting and biodegradable poly(β‐amino ester) polymer, and demonstrate its high ability to enter into cancer cells and release a combination of the anticancer drug doxorubicin and the non‐steroidal anti‐inflammatory drug indomethacin to achieve synergistic chemo‐anti‐inflammatory effects and overcome multidrug resistance. This study highlights the great potential of tumor targeting and dual stimuli‐responsive nanoparticles for an efficient delivery of multidrug combination to improve the cancer therapeutic efficacy. Abstract : Strong together : A strategy for the use of tumor‐targeting and pH/redox dual responsive nanoparticles for the controlled intracellular delivery of a combination of doxorubicin and indomethacin is demonstrated. The strategy allows synergistic chemo‐anti‐inflammatory effects and overcomes multidrug resistance (see figure; COX‐2=cyclooxygenase‐2).